Bridging soil mapping units and digital soil mapping through probability-driven machine learning: an uncertainty-aware framework for soil class prediction in Antarctica - Rafael G. Siqueira; Cássio M. Moquedace; Márcio R. Francelino; Carlos Ernesto G.R. Schaefer; Roberto F.M. Michel; Daniela Schmitz; Flávia R. Ferrari; Caroline Delpupo; Eduardo O. Senra; Heitor P. Palma; Daniel N. Krum; Fábio S. de Oliveira; et al. (CATENA, 2026)

eIF6 links histone acetylation with translational control of HDAC in skeletal muscle - Alessandra Scagliola; Annarita Miluzio; Ivan Ferrari; Daniel Brina; Sara Ricciardi; Stefano Biffo (Molecular and Cellular Biochemistry, 2026)
Skeletal muscle is crucial for glucose regulation and amino acid storage, significantly influencing overall metabolic balance. Its function is tightly regulated by complex mechanisms, with histone acetylation as a key epigenetic control point. Our previous work identified eIF6 as a key regulator of muscle energy homeostasis and demonstrated its role in modulating histone acetylation in the liver. However, whether similar epigenetic mechanisms underpin eIF6’s effects in muscle remains undetermined. To investigate this, we measured H3K9 acetylation levels and HDAC activity both in vivo, using eIF6 +/– mice, and in vitro, following eIF6 depletion. Our findings demonstrate that eIF6 downregulation in C2C12 myoblasts drives an increase in histone acetylation, a pattern also evident in heterozygous eIF6 primary satellite cells, both in their undifferentiated state and following differentiation. In vivo, eIF6 +/− mice show pronounced histone hyperacetylation, especially in younger animals, which correlates with a specific decrease in class II HDACs, particularly HDAC4 and HDAC5. This trend is further supported by in vitro data and findings from Drosophila eIF6 +/− mutants, both of which exhibit decreased HDAC activity. Importantly, the reduction in HDAC4 and HDAC5 activity appears to result from decreased protein levels, driven by eIF6-dependent translational regulation of their mRNAs. All together, these findings establish a link between mRNA translation and histone acetylation in muscle, underpinning translational control as a master regulator of histone acetylation.

Generative artificial intelligence and marine ecological monitoring - Luciano Ortenzi; Jacopo Aguzzi; Damianos Chatzievangelou; Eugenio Nerio Nemmi; Michele Ferrari; Ivan Masmitja; Morane Clavel-Henry; Nixon Bahamon; Nathan J. Robinson; Giacomo Picardi; Paula Espina; Simona Violino; et al. (Environmental Modelling & Software, 2026)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Assessing storm surge model performance: what error indicators can measure the model's skill? - Rodrigo Campos-Caba; Jacopo Alessandri; Paula Camus; Andrea Mazzino; Francesco Ferrari; Ivan Federico; Michalis Vousdoukas; Massimo Tondello; Lorenzo Mentaschi (Ocean Science, 2024)
A well-validated storm surge numerical model is crucial, offering precise coastal hazard information and serving as a basis for extensive databases and advanced data-driven algorithms. However, selecting the best model setup based solely on common error indicators like the root-mean-square error (RMSE) or Pearson correlation does not always yield optimal results. To illustrate this, we conducted 34-year high-resolution simulations for storm surge under barotropic (BT) and baroclinic (BC) configurations using atmospheric data from ERA5 and a high-resolution downscaling of the Climate Forecast System Reanalysis (CFSR) developed by the University of Genoa (UniGe). We combined forcing and configurations to produce three datasets: (1) BT-ERA5, (2) BC-ERA5, and (3) BC-UniGe. The model performance was assessed against nearshore station data using various statistical metrics. While RMSE and Pearson correlation suggest BT-ERA5, i.e., the coarsest and simplest setup, is the best model (followed by BC-ERA5), we demonstrate that these indicators are not always reliable for performance assessment. The most sophisticated model (BC-UniGe) shows worse values of RMSE or Pearson correlation due to the so-called “double penalty” effect. Here we propose new skill indicators that assess the ability of the model to reproduce the distribution of the observations. This, combined with an analysis of values above the 99th percentile, identifies BC-UniGe as the best model, while ERA5 simulations tend to underestimate the extremes. Although the study focuses on the accurate representation of storm surge by the numerical model, the analysis and proposed metrics can be applied to any problem involving the comparison between time series of simulation and observation.

Detection of archaeological structure on the slope ground using geophysical methods: The case of the Castle of Canossa - Annalisa Capurso; Lara De Giorgi; Ivan Ferrari; Francesco Giuri; Giovanni Leucci (Journal of Applied Geophysics, 2024)

Multichannel GPR and multi-depth electromagnetic surveys for the study of Villa Eucheria and Aquinum at Castrocielo (Frosinone, Central Italy) - Dora Francesca Barbolla; Ivan Ferrari; Francesco Giuri; Ilaria Miccoli; Giuseppe Scardozzi; Veronica Ferrari; Giovanni Leucci (Journal of Applied Geophysics, 2024)

Villa del Casale Piazza Armerina (EN): New data related to geophysical investigations - Isabella Baldini; Carla Sfameni; Lara De Giorgi; Dora Francesca Barbolla; Ivan Ferrari; Francesco Giuri; Chiara Torre; Giovanni Leucci (Journal of Applied Geophysics, 2024)

Evapotranspiration of an abandoned grassland in the Italian Alps: Modeling the impact of shrub encroachment - Davide Gisolo; Ivan Bevilacqua; Alessio Gentile; Justus van Ramshorst; Davide L. Patono; Claudio Lovisolo; Maurizio Previati; Davide Canone; Stefano Ferraris (Journal of Hydrology, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Carotid artery stenting during endovascular thrombectomy for acute ischemic stroke with tandem occlusion: the Italian Registry of Endovascular Treatment in Acute Stroke - Fabrizio Sallustio; Giovanni Pracucci; Manuel Cappellari; Valentina Saia; Alfredo Paolo Mascolo; Federico Marrama; Roberto Gandini; Giacomo Koch; Marina Diomedi; Federica D’Agostino; Alessandro Rocco; Valerio Da Ros; et al. (Acta Neurologica Belgica, 2023)

Medial prefrontal cortex involvement in aesthetic appreciation of paintings: a tDCS study - Zaira Cattaneo; Chiara Ferrari; Susanna Schiavi; Ivan Alekseichuk; Andrea Antal; Marcos Nadal (Cognitive Processing, 2020)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.